Extension of the Rotating Disk Electrode Method to Thin Samples of Non-Disk Shape. Issue 15 (25th October 2019) - Pohl, Marcus D.; Haschke, Sandra; Göhl, Daniel; Kasian, Olga; Bachmann, Julien; Mayrhofer, Karl J. J.; Katsounaros, Ioannis
Abstract : A straightforward approach is presented to make thin electrode samples of non-disk shape compatible with the rotating disk electrode method, by merely attaching the sample on the rotating shroud and confining the area exposed to the electrolyte using chemically resistant, adhesive material. The performance of an as prepared rotating E-beam evaporated platinum film is compared with that of a conventional rotating platinum disk for three classical electrochemical reactions: the carbon monoxide oxidation, the hydrogen oxidation, and the oxygen reduction. Despite the unusual electrode morphology that deviates from the ideal rotating disk electrode configuration, the results and conclusions for the rotating E-beam evaporated film are equivalent to those for the classical rotating disk. Thus, this approach enables investigations under well controlled mass transport conditions using non-conventional thin electrode samples.